American Populism and the New Political Economy of the Media Field - Jutel, Olivier (The Political Economy of Communication, 2013)
The emergence of the Tea Party as a specifically mediatized, populist movement owing its success to its close affiliation with Fox News, is emblematic of the new political economy of the media field. Within the mediatized social space, populist notions of 'authenticity' have become the economic and cultural capital of the media field, superseding the liberal unified public. Audiences no longer merely consume media, but actively construct the very communication networks that are used by media corporations to scrutinize the minutia of personal taste preferences. In incorporating forms of free audience labor, the media simultaneously perfect the audience commodity while opening up the field of power to the social logics of difference and equivalence which constitute the political. Fox News viewers do not simply consume the news but generate it as Tea Party protestors. This new logic of commodification and the incorporation of free labor signal the positive agency of mediatized subjects.